2013
DOI: 10.1124/dmd.113.053397
|View full text |Cite|
|
Sign up to set email alerts
|

Meeting the Challenge of Predicting Hepatic Clearance of Compounds Slowly Metabolized by Cytochrome P450 Using a Novel Hepatocyte Model, HepatoPac

Abstract: Generating accurate in vitro intrinsic clearance data is an important aspect of predicting in vivo human clearance. Primary hepatocytes in suspension are routinely used to predict in vivo clearance; however, incubation times have typically been limited to 4-6 hours, which is not long enough to accurately evaluate the metabolic stability of slowly metabolized compounds. HepatoPac is a micropatterened hepatocyte-fibroblast coculture system that can be used for continuous incubations of up to 7 days. This study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(127 citation statements)
references
References 59 publications
8
119
0
Order By: Relevance
“…The twofold lower underprediction average for predicted clearances in HepatoPac® was in line with the twofold higher metabolic activity in HepatoPac® as compared to the suspension cultures from the same donor. Our results agree well with the finding of Chan et al (10), who also reported a twofold higher metabolic capacity in HepatoPac® compared to suspended hepatocytes from a different donor and using different model compounds. For low-clearance compounds, warfarin and tolbutamide, the long-term system was clearly superior for the prediction of hepatic clearances as no clearance values could be determined in the suspension cultures.…”
Section: Ivive Of In Vitro Clearance Assessmentssupporting
confidence: 83%
See 3 more Smart Citations
“…The twofold lower underprediction average for predicted clearances in HepatoPac® was in line with the twofold higher metabolic activity in HepatoPac® as compared to the suspension cultures from the same donor. Our results agree well with the finding of Chan et al (10), who also reported a twofold higher metabolic capacity in HepatoPac® compared to suspended hepatocytes from a different donor and using different model compounds. For low-clearance compounds, warfarin and tolbutamide, the long-term system was clearly superior for the prediction of hepatic clearances as no clearance values could be determined in the suspension cultures.…”
Section: Ivive Of In Vitro Clearance Assessmentssupporting
confidence: 83%
“…The in vitro clearances were then scaled by applying the well-stirred model using the conventional approach as described in BMATERIALS AND METHODS^(Eqs. [8][9][10][11][12]. Fraction unbound values in the incubation media and human plasma were experimentally determined and are listed in Table III together with the blood-to-plasma ratios.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When cultured in this way, it was shown that drug-metabolizing enzyme activities were sustained for several days without a change in medium, thereby yielding the potential to carry out long drug metabolism incubations potentially ideal for measuring reliable consumption rates of low-CL int compounds. This was demonstrated by Chan et al (22), for several drugs, including low-CL int drugs theophylline, diazepam, tolbutamide, meloxicam, among others using hepatocytes from three individual donors. As with the Liverchip method, it was low-CL int drugs that were best predicted, with high-CL int drugs underpredicted.…”
Section: Hepatocyte Culture Systemsmentioning
confidence: 93%